THE JADID MOVEMENT IN TURKESTAN AND THEIR ACTIVITIES - Bo‘ronov , Shohzod (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article provides information on the emergence of the Jadid movement in Turkestan and the study of their activities, their actions and activities, their work for the nation and the work they did for freedom and liberty. This article scientifically analyzes the factors of the emergence of the Jadid movement, the main ideas and areas of activity that arose in Turkestan in the late 19th and early 20th centuries. The role of Jadids in education, the press, literature and political life is highlighted, and the historical significance of this movement is revealed..